Two crates of beer and 40 pizzas: the adoption of innovative political behavioural targeting techniques - Tom Dobber; Damian Trilling; Natali Helberger; Claes H. de Vreese (Internet Policy Review)
Political campaigns increasingly use data to (micro)target voters with tailored messages. In doing so, campaigns raise concerns about privacy and the quality of the public discourse. Extending existing research to a European context, we propose and test a model for understanding how different contextual factors hinder or facilitate data-driven capabilities of campaigns. We applied the model during the 2017 national election campaign in the Netherlands. The results show how data-driven targeting techniques are not only useful in a first-past-the-post system, but also in a proportional representation system, which at first sight seems to be less suitable for such techniques.